Challenges Facing a Deaf Family Member Concerning a Loved One’s Dying - Kehl, Karen A. (2009)
Individuals who are Deaf face challenges both similar and unique from those faced by hearing individuals when a family member is dying. This study was guided by the question “What are the challenges faced by a Deaf family member when a loved one is dying?” Methods - This qualitative study is guided by critical theory and an interpretive perspective. Robert, a college-educated older adult who has been Deaf from birth was interviewed in American Sign Language using a death history format. Results – There are challenges for Deaf family members that affect communication with both the dying person and health care professionals. Patient-family communication issues included physical challenges and financial challenges. Lack of cultural competence concerning the Deaf community created challenges communicating with professionals. Decision-making was also a challenge. CONCLUSIONS: These findings provide a framework for future research concerning the needs of Deaf individuals facing the end of life and provide guidance for clinicians.